A review of research on learning support in mathematics education in Sub-Saharan Africa: The case of Botswana, Namibia, Zambia and Zimbabwe - February Pamela J.; Hamukwaya Shemunyenge Taleiko; Hamukwaya Shindume Lomboleni; Jatileni Cloneria Nyambali (Kaplan Higher Education Academy, 2022)
All learners have different educational needs, and learners taking mathematics are no exception. This review paper focuses on the recent studies in Sub-Saharan Africa in four countries: Namibia, Botswana, Zimbabwe, and Zambia in mathematics education. These countries perform poorly in mathematics according to all SACMEQ (Southern and Eastern Africa Consortium for Monitoring Educational Quality) reports, though there has been an incremental improvement. The methodology of the study incorporated research studies on mathematics learning disabilities and difficulties, however, only limited research was found in Namibia and none in the other countries using this terminology. In all four countries, the inclusive education policies do not specifically mention MLD. As a result, this study was expanded to include learners’ performance in mathematics in general. The articles sought were research-based articles and were mainly empirical for the period 2010 to 2021. Most research focuses on problems related to poor performance of learners, teachers' and learners’ perceptions and attitudes, and teacher training in mathematics education. These issues are compared and contrasted in different countries. The limited research found on MLD focuses on beliefs, misconceptions, barriers in teaching and learning mathematics, and learning support. We recommend that in these four countries, more research is needed on learners with MLD within the general mathematics population. The focus area should include early identification of learners with MLD, support based on the diagnosed learning needs, and teacher training on MLD, appropriate teaching and learning strategies.